Magnetic Lattices for Ultracold Atoms - Tran, Tien Duy; Wang, Yibo; Glaetzle, Alex; Whitlock, Shannon; Sidorov, Andrei; Hannaford, Peter (Communications in Physics, 2019)
This article reviews the development in our laboratory of magnetic lattices comprising periodic arrays of magnetic microtraps created by patterned magnetic films to trap periodic arrays of ultracold atoms. Recent achievements include the realisation of multiple Bose-Einstein condensates in a 10 \(μ\)m-period one-dimensional magnetic lattice; the fabrication of sub-micron-period square and triangular magnetic lattice structures suitable for quantum tunnelling experiments; the trapping of ultracold atoms in a sub-micron-period triangular magnetic lattice; and a proposal to use long-range interacting Rydberg atoms to achieve spin-spin interactions between sites in a large-spacing magnetic lattice